Numerical and Experimental Study on the Air Convective Heat Transfer Characteristics in Large-Scale Rectangular Channel with Asymmetric Heating Considering the Influence of Entry Form. (3rd October 2019) - Du, Kashuai; Hu, Po; Zhang, Lefu; Wang, Weibo
Abstract: In the passive containment cooling system (PCCS) of an AP1000-type pressurized water reactor nuclear power plant, the air convective heat transfer in the external channel of the containment plays a key role under accident conditions. In this study, the containment external channel is simplified into a large-scale rectangular channel with asymmetric heating, and an experimental and numerical study is conducted to evaluate the air heat transfer characteristics. In addition, the effect of the entry form, which comprises an irregular inlet duct and a pore plate, is considered. First, the results show that heat transfer is enhanced by the entry form, which can be verified by numerical simulation and experiment. Second, when analyzing the air heat transfer characteristics of the actual PCCS annular channel, the Gnielinski correlation is relatively conservative since this correlation hugely underestimates the heat transfer rate of numerical cases in a large-scale rectangular channel with the entry form.